COMPARATIVE ANALYSIS OF MEN'S AND WOMEN'S LANGUAGE USE IN ENGLISH AND KARAKALPAK - Alfiya Amangeldieva (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2026)
The article studies how men and women speak differently in English and Karakalpak which are two languages that belong to different cultural and sociolinguistic traditions. The article presents evidence that speech patterns of men and women show universal tendencies and yet their particular expressions depend on social hierarchy systems and the linguistic characteristics of each community. The research results offer new insights about how gender functions as a sociolinguistic element in Western and Central Asian linguistic traditions.